Acute Procedural Results of Pulsed Field Cryoablation for Persistent Atrial Fibrillation: Multicenter First-in-Human PARALELL Trial - Essebag, Vidal; Boersma, Lucas; Petru, Jan; Gallagher, Mark M; Reddy, Vivek Y; De Potter, Tom; Derejko, Pawel; Neuzil, Petr; Grigorov, Ilya; Verma, Atul (Journal of cardiovascular electrophysiology, 2025)
INTRODUCTION: Pulsed Field Cryoablation (PFCA) is a dual-energy cardiac ablation modality consisting of short-duration ultra-low temperature cryoablation (ULTC) followed immediately by pulsed field ablation (PFA) delivered from the same catheter. It is hypothesized that PFCA may improve contact stability during PFA, while maintaining lesion depth and effectiveness of ULTC. METHODS: PARALELL is a first-in-human multicenter study evaluating safety and effectiveness of a novel PFCA catheter and system in patients with persistent atrial fibrillation (PsAF) using the combination of pulmonary vein (PVI) and posterior wall (PWI) isolation. RESULTS: Sixty-six patients were ablated at six sites. One groin hematoma and one intubation-related hospitalization were the only serious procedure- or device-related adverse events recorded in the study. Per protocol, acute effectiveness was evaluated in 46 patients, including 31 patients with post-hoc analysis of cryogenic energy per lesion. After an average of 21.1 ± 9.3 lesions per patient the rates of PVI and PWI were 95.7% (176/184) and 97.7% (42/43), respectively. The average cryogenic energy per patient was highly predictive of acute isolation success with ROC AUC = 0.944% and 100% rates of both PVI and PWI in 24 patients in the optimal energy cohort. Grade I microbubbles and faint muscle contractions were detected in 1.1% and 0.5% of ablations, respectively. CONCLUSION: This initial multi-center experience suggests that PFCA can be efficiently performed for PVI and PWI using a single versatile catheter system, with high acute success and good early safety profile. The evaluation of the chronic 12-month effectiveness of PFCA is ongoing.
Keywords: výsledek terapie; Cryosurgery; Male; Risk Factors; Equipment Design; Heart Rate; Aged; mužské pohlaví; senioři; srdeční frekvence; design vybavení; Atrial Fibrillation; Treatment Outcome; Pulmonary Veins; Time Factors; lidé; akční potenciály; Action Potentials; ženské pohlaví; Cardiac Catheters; Humans; časové faktory; rizikové faktory; kryochirurgie; venae pulmonales; Female; lidé středního věku; srdeční katétry; fibrilace síní; Middle Aged